Application of Rainfall Threshold for Sediment-Related Disasters in Malaysia: Status, Issues and Challenges - Ligong S.; Sidek L.M.; Hayder G.; Mohd Dom N. (MDPI, 2023)
Developing countries; Disasters; Economics; Landslides; Rain; Sediments; Critical rainfall; Energy; Human lives; Hydropower; Issues and challenges; Malaysia; Mudflow; Natural disasters; Rainfall thresholds; Sediment-related disaster; Debris; catastrophic event; correlation; damage mechanics; debris flow; disaster management; hydroelectric power; landslide; mudflow; natural disaster; prediction; rainfall; socioeconomic conditions; threshold; Malaysia